Nuovi modelli procreativi, diritto allo status e principi di ordine pubblico (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The essay analyzes the legal position in the Italian legal system of the child born of same sex couples, including through surrogacy. In this context, the value of the individual represents the lowest common denominator of the persons’ rights and this should be considered the current scope of the international public order concept.
Keywords: Protection; Child; Status; Surrogacy; Public order